2014
DOI: 10.1111/1744-7917.12163
|View full text |Cite
|
Sign up to set email alerts
|

Responses of 9 lepidopteran species to Bacillus thuringiensis: How useful is phylogenetic relatedness for selecting surrogate species for nontarget arthropod risk assessment?

Abstract: To evaluate phylogenetic relatedness as a proxy for susceptibility to Bacillus thuringiensis (Bt) when selecting species to act as surrogates for others in prerelease testing, we examined the responses of 11 laboratory-reared lepidopteran colonies, comprising members of 2 families, 5 genera, and 9 species, to a commercial Bt preparation. Survival, pupal mass, and timing of pupation and adult emergence of 2 noctuids (Spodoptera litura and Helicoverpa armigera) and 7 tortricids (Cnephasia jactatana, Ctenopseusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Previous studies have observed phylogenetic relatedness as a predictive factor for toxicity among related species for other contaminants (e.g. endosulfan, zinc, Bacillus thuringiensis toxin) [5254]. Our results provide support for the notion that phylogenetic relatedness may be useful for predicting toxicity of clothianidin and possibly other neonicotinoids in aquatic invertebrates.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have observed phylogenetic relatedness as a predictive factor for toxicity among related species for other contaminants (e.g. endosulfan, zinc, Bacillus thuringiensis toxin) [5254]. Our results provide support for the notion that phylogenetic relatedness may be useful for predicting toxicity of clothianidin and possibly other neonicotinoids in aquatic invertebrates.…”
Section: Discussionsupporting
confidence: 83%
“…Other recent studies reporting about Bt effects on Lepidoptera larvae were less relevant for the following reasons: they focused on Bt sprays instead of Cry proteins or Cry maize pollen (Burgess et al (2015); they studied lepidopteran pest species instead of non-target species (Erasmus et al 2010(Erasmus et al , 2014Mahmoud et al 2011;Pérez-Hedo et al 2012;Munoz et al 2014); they were done with transgenic crops other than maize (Kjaer et al 2010); they investigated nectar feeding rather than pollen feeding (Paula et al 2014); or they studied exposure rather than direct toxic effects (Lang and Otto 2015;Lövei et al 2020). In total, the literature map includes 25 publications, of which 21 reporting on laboratory experiments with 17 different species, and 6 on field studies with diverse specimens (see Appendix A).…”
Section: Literature Mapsmentioning
confidence: 99%
“…However, since 2010, only one further research paper about Bt maize pollen effects on non-target Lepidoptera has been published [6]. Other recent studies reporting on Bt effects on Lepidoptera larvae focused on Bt sprays instead of Cry proteins or Cry maize pollen [13], studied lepidopteran pest species and not non-target species [14][15][16][17][18], were done with transgenic crops other than maize [19], investigated nectar feeding rather than pollen feeding [20], or studied exposure rather than direct toxic effects [21,22].…”
Section: Introductionmentioning
confidence: 99%